Analisis dan Desain User Interface dan User Experience dengan Pendekatan User Persona Berbasis Design Thinking - Reva Eka Prasetyo; Tan Amelia; Julianto Lemantara (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Picnicker is a startup that is engaged in tourism where its services provide information for tourists who want to find it easy to find information and gain access to local tourist attractions by purchasing tickets online and validating entry to tourist attractions without queuing to reduce the risk of contracting Covid-19 in the middle of the world. pandemic. The current problem is that the Picnicker startup requires a platform that can accommodate a collection of information about tourist destinations, tourist locations, and tourist attraction tickets in forming a product that will be built to achieve a minimum viable product (MVP), which of course has aspects, one of which is the User Interface and User Experience. This study uses the Design Thinking method which there are 5 stages, namely empathize, define, ideate, prototype, and test. In addition, the reason for using the Design Thinking method is because of the process of creating new innovative ideas to solve problems in developing new application products and for measuring user experience using the HEART Metric framework developed by Google to measure the level of success of UX on a product. Based on the analysis and design of the user interface and user experience at the Picnicker startup with a user persona approach based on design thinking, the success of User Experience carried out using the Google Heart Metric Framework was 0.762 and greater than r-table 0.284 by performing a reliable test using Cronbach Alpha which is shown to 23 questions and from the Heart Metric Framework indicators there are 5 indicators, namely happiness, engagement, adaptation, retention, and task success where the average percentage is 55.1%, which means that overall the results obtained indicate that users are acceptable and get a range of the good one.